Tensegrity-Inspired Joint Can Protect from Impacts by Isolating - Walter, Jonas; Rothfischer, Lukas; Stierstorfer, Richard; Nemoto, Takeru; Franke, Jörg; Reitelshöfer, Sebastian (Mechanisms and Machine Science, 2023)
Cable-driven parallel robots are known for their highly dynamic motions. At the same time, tensegrity robots are considered to be robust due to their intrinsic compliance. In a previous work, it was shown that a cable-driven joint with a tensegrity-inspired design allows fast rotations. The question remains whether such a joint is not only fast, but could also protect its base link from impacts due to its special design. In this paper, it is shown that a tensegrity-inspired joint can protect from impacts by isolating. A hardware prototype of such a joint was loaded with a modal hammer. It was found that the joint isolates impact forces up to 83%, demonstrating its ability to effectively absorb and dissipate energy from external impacts. Putting the results in a more general context, such a joint, however, can be used not only (a) passively to protect a base link, but also (b) actively for high-speed motions of a follower link by pulling a lightweight mass with parallel attached and actuated cables. It is anticipated that this study could be a starting point for the creation of novel robotic kinematics, composed of conventional and tensegrity kinematics, to build fast and robust robots.
CRIS-Team Scopus Importer:2023-11-17
Keywords: Cable-Driven Joint; Impact Protection; Tensegrity